Meta Analysis: Application of Health Belief Model Theory on COVID-19 Acceptance in General Population - Resta Dwi Yuliani; Hanung Prasetya; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: The COVID-19 vaccine is an effective strategy to prevent viral infection during global pandemic. Health belief model has been recommended to explain the acceptance of COVID-19 vaccination behavior in the community. This study aimed to estimate the perceived susceptibility to COVID-19 and the perceived benefit in receiving the COVID-19 vaccine.Subjects and Method: This study used a systematic review study design and a meta-analysis using PICO, Population: Society, Intervention: Perceptions of high susceptibility to COVID-19 and high perceptions of benefits about the COVID-19 vaccine. Comparison: Low perceived susceptibility to COVID-19 and low perceived benefit of COVID-19 vaccine, Outcome: Acceptance of COVID-19 vaccine. The articles used in this study came from 4 databases, namely Pubmed, Sciencedirect, SpringerLink and Google Scholar. The keywords used in the article search were as follows “Health Belief Model” OR “HBM” AND “Acceptance” OR “Receive” AND “COVID-19 Vaccine” AND “General Population”. The articles included in this study were full paper articles, cross sectional study designs, in 2020-2022 and the size of the relationship of Adj Odds Ratio (aOR).Results: A total of 9 cross-sectional studies with 12,713 people from 3 continents, namely America (United States), Asia (Bangladesh, China, Hong Kong, Lebanon, and Saudi Arabia) and Europe (Russia) were obtained. From data processing, it was found that a high perceived susceptibility to COVID-19 increased acceptance of COVID-19 vaccination by 1.33 times compared to a low perceived susceptibility and this result was statistically significant (aOR= 1.33; 95% CI= 1.08 to 1.65; p= 0.008) . A high perceived benefit increased acceptance of COVID-19 vaccination by 3.28 times compared to a low perceived benefit and this result was statistically significant (aOR= 3.28; CI 95%= 1.87 to 5.74; p< 0.001).Conclusion: Perceived susceptibility and perceived benefit increase the likelihood of acceptance of the COVID-19 vaccination in the community. Keywords: Health Belief Model, perceived susceptibility, perceived benefit, COVID-19 vaccination.Correspondence:Resta Dwi Yuliani. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: restadwi24@gmail.com. Mobile: +6285731288002Journal of Health Promotion and Behavior (2022), 07(03): 225-237DOI: https://doi.org/10.26911/thejhpb.2022.07.03.05